2017
DOI: 10.1371/journal.pntd.0005853
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Schistosoma mansoni with miltefosine in vitro enhances serological recognition of defined worm surface antigens

Abstract: BackgroundMiltefosine, an anti-cancer drug that has been successfully repositioned for treatment of Leishmania infections, has recently also shown promising effects against Schistosoma spp targeting all life cycle stages of the parasite. The current study examined the effect of treating Schistosoma mansoni adult worms with miltefosine on exposure of worm surface antigens in vitro.Methodology/Principal findingsIn an indirect immunofluorescence assay, rabbit anti-S.mansoni adult worm homogenate and anti-S. manso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 101 publications
3
19
1
Order By: Relevance
“…43 More recently, MFS was shown to unmask parasite surface antigens not normally exposed to the host during infection, enhancing their serological recognition. 53 In the present study, inclusion of MFS and OA in PZQ-OA-MFS-LNCs did not significantly enhance antischistosomal activity (Tables 2 and 3), probably because of the lower MFS dose used (10 mg/kg) and masking of OA effects by Span 80 (sorbitan monoleate), reported to exert a fusogenic effect on phospholipid vesicles. 54 PK data indicated an increased PZQ bioavailability (Table 4), contributing to an enhanced PD activity by LNCs.…”
Section: Discussioncontrasting
confidence: 47%
“…43 More recently, MFS was shown to unmask parasite surface antigens not normally exposed to the host during infection, enhancing their serological recognition. 53 In the present study, inclusion of MFS and OA in PZQ-OA-MFS-LNCs did not significantly enhance antischistosomal activity (Tables 2 and 3), probably because of the lower MFS dose used (10 mg/kg) and masking of OA effects by Span 80 (sorbitan monoleate), reported to exert a fusogenic effect on phospholipid vesicles. 54 PK data indicated an increased PZQ bioavailability (Table 4), contributing to an enhanced PD activity by LNCs.…”
Section: Discussioncontrasting
confidence: 47%
“…The mechanism of action of miltefosine may depend on the interplay between parasite and host. Thus, El-Faham and colleagues [45] demonstrated that treating parasites with miltefosine enhances serological recognition of defined adult worm surface antigens. The absence of activity here may suggest a stage-specific mode of action, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The schistosomicidal action of ARA is based on excessive hydrolysis of parasite surface membrane SM. Interestingly, Miltefosine, a hexa -decyl-phosphocholine, which interferes with proper biosynthesis of SM, was recently documented as a potent schistosomicide in vitro and in vi vo [106] .…”
Section: Schistosomicidal Actionmentioning
confidence: 99%
“…Disruption of the tight SM-based hydrogen bond network around cancer cells may allow contact inhibition processes to proceed and cell proliferation to stop [77] , whereby the primary SM catabolite, ceramide released following SM hydrolysis is a renowned secondary messenger involved in programmed cell death [117] . It is of importance to recall that Miltefosine, which has been approved for the treatment of breast cancer metastasis, and is currently used for the treatment of cutaneous metastases of mammary carcinoma significantly inhibits SM biosynthesis in human hepatoma and other tumor cells [106] , [118] , [119] , [120] , [121] . The likely mechanism of action of this phospholipid analogue is inhibition of phosphatidylcholine biosynthesis, thus hindering SM metabolism, and substantially increasing the levels of ceramide [120] , [121] .…”
Section: Tumoricidal Potentialmentioning
confidence: 99%